Global unions, global business. Global union federations and international business - Croucher, Richard; Cotton, Elizabeth (Enfield, 2009)
"Global Unions, Global Business looks at a little-understood aspect of globalisation: the role of the Global Union Federations in international employment relations. The book outlines the way that trade unions at international level relate to multinational companies using detailed and up-to-date illustrations of their activities. Importantly, the book includes an in-depth case study of one GUF's dealings with a major multinational company. Throughout the book the authors also explore the previously unknown internal lives of the Global Union Federations and propose ideas about how they can strengthen their position internationally.